Large-scale apple GWAS reveals NAC18.1 as a master regulator of ripening traits - Sophie Watts; Zoë Migicovsky; Sean Myles (Fruit Research, 2023)
Apple quality traits such as fruit texture, sugar content, and firmness retention during storage are key targets for breeders. Understanding the genetic control of fruit quality traits can enable the development of genetic markers, useful for marker-assisted breeding of new apple cultivars. We made use of over 260,000 single nucleotide polymorphisms (SNPs) genotyped across 1,054 apple accessions from Canada's Apple Biodiversity Collection to perform genome-wide association for 21 fruit quality and phenology traits. We identified two loci on chromosome 15 and 16 associated with phenolic content and a locus on chromosome 10 associated with softening. In addition, we determined that allelic variation at the NAC18.1 transcription factor was associated with numerous traits including harvest date, firmness at harvest, and firmness after storage. Our analyses suggest that NAC18.1 independently acts as a high level regulator of multiple ripening related traits and we propose a model for the allelic effects at NAC18.1 on apple ripening and softening.